A Strategic Choice: The State Policy Requirement in Core International Crimes. (30th October 2015) - CHOULIARAS, ATHANASIOS
Abstract: The article focuses on one of the most intriguing and, at the same time, controversial issues of international criminal law: whether the state policy requirement should be considered as a constitutive element in core international crimes. Adopting a criminal policy perspective, my intention is to contribute to the ongoing discussion by offering a doctrinal and criminological corroboration of the position that answers in the affirmative. Nevertheless, I am not necessarily promoting a normative choice entailing the amendment of the definition of core international crimes, but I rather call for a policy choice of focusing on cases that presume a state policy component.